Analysis of an M|G|1|R queue with batch arrivals and two hysteretic overload control policies - Gaidamaka, Yuliya; Pechinkin, Alexander; Razumchik, Rostislav; Samouylov, Konstantin; Sopin, Eduard (Zielona Góra: Uniwersytet Zielonogórski)
Hysteretic control of arrivals is one of the most easy-to-implement and effective solutions of overload problems occurring in SIP-servers. A mathematical model of an SIP server based on the queueing system with batch arrivals and two hysteretic loops is being analyzed.
Keywords: queueing system; batch arrival; general service time; overload; hysteretic load control